Bases of power and conflict intervention strategy: a study on Turkish managers. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – This study aims to develop an influence perspective for managerial intervention in subordinates conflicts, which helps to represent various strategies identified in the literature in a single model. Managers' power base was then related to their intervention strategies. Drawing upon Social Judgment Theory, anchoring of subordinates positions is studied as a moderating variable.Design/methodology/approach – Thirty nine supervisors and their 165 subordinates from several organizations in Turkey filled out a questionnaire reporting power base of supervisor and their intervention strategy utilizing the critical incident technique.Findings – Referent power of superior led to mediation in subordinates' conflicts. However, mediation decreased while restructuring, arbitration, and educative strategies increased with increased anchoring of subordinates' positions. These latter strategies mostly relied on reward power of manager. Subordinate satisfaction was highest with mediation and lowest when supervisors distanced themselves from the conflict.Research limitations/implications – The present study could only test the moderating effect of escalation as an anchoring variable. Future studies may look at the anchoring effect of whether the dispute is handled in public or in private, and whether the parties have a competing versus collaborative or compromising styles.Practical implications – Training of managers in mediation may be essential in cultures where they play a focal role in handling subordinates conflicts. Such training may have to take into account their broader influence strategies and use of power.Originality/value – An influence perspective is useful in integrating the vast array of managerial intervention strategies in the literature. Furthermore, the anchoring effect provides a theoretical explanation for managers' use of more forceful intervention with less cooperative subordinates.